2020
DOI: 10.1007/s10822-020-00325-x
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking GPCR homology model template selection in combination with de novo loop generation

Abstract: G protein-coupled receptors (GPCR) comprise the largest family of membrane proteins and are of considerable interest as targets for drug development. However, many GPCR structures remain unsolved. To address the structural ambiguity of these receptors, computational tools such as homology modeling and loop modeling are often employed to generate predictive receptor structures. Here we combined both methods to benchmark a protocol incorporating homology modeling based on a locally selected template and extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The internal dataset used to develop our random forest classifier (Figure 1, ligandreceptor complex types 5 and 6) required modeled structures for the 5 DUD-E GPCR targets (AA2AR, ADRB1, ADRB2, CXCR4, and DRD3). For each DUD-E GPCR target, a set of three homology models representing "best" and "normal" cases for template selection were constructed using our benchmarked homology modeling protocol (Table 4) [29][30][31]. We chose to develop multiple homology models for each target (rather than just a single homology model) to reflect the range of information that may or may not be available for any GPCR target at the center of a ligand identification study.…”
Section: Protein Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…The internal dataset used to develop our random forest classifier (Figure 1, ligandreceptor complex types 5 and 6) required modeled structures for the 5 DUD-E GPCR targets (AA2AR, ADRB1, ADRB2, CXCR4, and DRD3). For each DUD-E GPCR target, a set of three homology models representing "best" and "normal" cases for template selection were constructed using our benchmarked homology modeling protocol (Table 4) [29][30][31]. We chose to develop multiple homology models for each target (rather than just a single homology model) to reflect the range of information that may or may not be available for any GPCR target at the center of a ligand identification study.…”
Section: Protein Modelingmentioning
confidence: 99%
“…However, observed RMSD values support the use of the CoINPocket similarity score as a metric for homology model template selection regardless of whether a template structure binding to the same endogenous ligand as the target GPCR being modeled is available. For the external dataset, four modeled structures were generated or retrieved for each target: one was constructed with our in-house GPCR modeling protocol [29][30][31], two were retrieved from GPCRdb [26], and one was retrieved from the AlphaFold Protein Structure Database [33]. When generating the in-house homology model for each target in the external dataset, template structures were selected using the CoINPocket similarity metric [30], and loop modeling was again performed after the determination of loop anchor residues (Table S3).…”
Section: Protein Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous benchmarking studies have been conducted by incorporating global and local similarity measures to select the appropriate template for GPCRs. Models based on local similarity measures have produced better results in virtual screening experiments ( Castleman et al, 2019 ; Szwabowski et al, 2020 ). Multiple studies have shown that sequence identity above 30% could result in good GPCR homology models (within 3 Å) ( Shahaf et al, 2016 ; Loo et al, 2018 ; Jaiteh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%